Acute exacerbation in rheumatoid arthritis-associated interstitial lung disease: a retrospective case control study. Issue 9 (12th September 2013) - Hozumi, Hironao; Nakamura, Yutaro; Johkoh, Takeshi; Sumikawa, Hiromitsu; Colby, Thomas V; Kono, Masato; Hashimoto, Dai; Enomoto, Noriyuki; Fujisawa, Tomoyuki; Inui, Naoki; Suda, Takafumi; Chida, Kingo
Abstract : Objectives: To investigate the risk factors and prognosis associated with acute exacerbation (AE) in patients with rheumatoid arthritis-associated interstitial lung disease (RA-ILD). Design: A retrospective case–control study. Setting: A single academic hospital. Participants: 51 consecutive patients diagnosed with RA-ILD between 1995 and 2012. All patients fulfilled the diagnostic criteria of the American College of Rheumatology for RA. ILD was diagnosed on the basis of clinical presentation, pulmonary function tests, high-resolution CT (HRCT) findings and lung biopsy findings. Main outcome measures: Overall survival and cumulative AE incidence were analysed using Kaplan-Meier method. Cox hazards analysis was used to determine significant variables associated with AE occurrence and survival status. Results: A total of 11 patients (22%) developed AE, with an overall 1-year incidence of 2.8%. Univariate analysis revealed that older age at ILD diagnosis (HR 1.11; 95% CI 1.02 to 1.21; p=0.01), usual interstitial pneumonia (UIP) pattern on HRCT (HR 1.95; 95% CI 1.07 to 3.63; p=0.03) and methotrexate usage (HR 3.04; 95% CI 1.62 to 6.02; p=0.001) were associated with AE. Of 11 patients who developed AE during observation period, 7 (64%) died of initial AE. In survival, AE was a prognostic factor for poor outcome (HR 2.47; 95% CI 1.39 to 4.56; p=0.003). Conclusions: In patients with RA-ILD, older age at ILD diagnosis, UIP pattern on HRCT and methotrexate usage are associated with the development of AE. Furthermore, AE has a serious impact on their survival.